A Rationale for Going Back to the Future: Use of Disposable Spacers for Pressurised Metered Dose Inhalers. (27th September 2015) - Sanders, Mark; Bruin, Ronald
Abstract : The introduction of pressurised metered dose inhalers (MDIs) in the mid-1950s completely transformed respiratory treatment. Despite decades of availability and healthcare support and development of teaching aids and devices to promote better use, poor pMDI user technique remains a persistent issue. The main pMDI user aid is the spacer/valved holding chamber (VHC) device. Spacer/chamber features (size, shape, configuration, construction material, and hygiene considerations) can vie with clinical effectiveness (to deliver the same dose as a correctly used pMDI), user convenience, cost, and accessibility. Unsurprisingly, improvised, low-cost alternatives (plastic drink bottles, paper cups, and paper towel rolls) have been pressed into seemingly effective service. A UK law change permitting schools to hold emergency inhalers and spacers has prompted a development project to design a low-cost, user-friendly, disposable, and recyclable spacer. This paper spacer requires neither preuse priming nor washing, and has demonstrated reproducible lung delivery of salbutamol sulphate pMDI, comparable to an industry-standard VHC, an alternative paperboard VHC, and pMDI alone. This new device appears to perform better than these other VHC devices at the low flow rates thought achievable by paediatric patients. The data suggest that this disposable spacer may have a place in the single-use emergency setting.